2013
DOI: 10.1111/joa.12129
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical characterisation of olfactory ensheathing cells of zebrafish

Abstract: Continuous lifelong neurogenesis is typical of the vertebrate olfactory system. The regenerative ability of olfactory receptor neurons is dependent on the glial cell type specific to the olfactory pathway, designated 'olfactory ensheathing cells'. Several studies to date have focused on mammalian olfactory ensheathing cells, owing to their potential roles in cell-based therapy for spinal cord injury repair. However, limited information is available regarding this glial cell type in non-mammalian vertebrates, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 99 publications
1
21
0
Order By: Relevance
“…Our analysis, therefore, capitalizes on the deep evolutionary relationship between EmT, amygdala, and the sense of smell. Like rodents, zebrafish are macrosmatic animals whose reproductive behavior is hugely influenced by pheromones (Lazzari et al, 2014). Male zebrafish exposed to the female sex pheromone prostaglandin F2α (PGF2α) express stereotypic nudging behavior and conspecific male-male aggression (Sorensen et al, 1988;Yabuki et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Our analysis, therefore, capitalizes on the deep evolutionary relationship between EmT, amygdala, and the sense of smell. Like rodents, zebrafish are macrosmatic animals whose reproductive behavior is hugely influenced by pheromones (Lazzari et al, 2014). Male zebrafish exposed to the female sex pheromone prostaglandin F2α (PGF2α) express stereotypic nudging behavior and conspecific male-male aggression (Sorensen et al, 1988;Yabuki et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…To distinguish between Schwann cells and OEC, numerous molecular markers have been used to compare their immunochemical properties. Previous studies reported that both OEC and Schwann cells are immunopositive for S‐100 and GFAP and immunonegative for EMA . In contrast, OEC show negative staining for Leu7, which is positive in the peripheral nerve sheath and schwannomas .…”
Section: Discussionmentioning
confidence: 93%
“…Schwann cells and OECs have been described as two different types of cells that share microscopic aspects and many structural, behavioral, and immunohistochemical properties . Both OGS and OECT can present the same microscopic aspect of a typical schwannoma with elongated cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations